Populism versus Technocracy? Populist Responses to the Technocratic Nature of the EU - Reiser, Marion (2020)
While populism and technocracy have attracted enormous scientific attention in recent years, surprisingly how the two concepts relate to each other has rarely been investigated. Looking at the case of the EU, we investigate how populist parties position themselves in relation to technocracy in general and the technocratic nature of EU institutions in particular. In a first theoretical step, we identify the core elements, modes of governance, and policy output of technocratic governance and use them to derive potential responses of populist parties. In the empirical part, we investigate these aspects of technocracy by applying quantitative and qualitative approaches using the 2019 European election manifestos of 12 populist parties. We show that left- and right-wing populist parties articulate anti-technocratic positions, particularly regarding the core elements of technocratic governance. The concrete technocratic critique differs regarding the respective host ideology. However, within the group of hybrid populist parties, ANO 2011 and GERB appear not to have a critical stance towards technocracy and thus can be classified as technocratic populist parties.